Baryon acoustic oscillations in the Dark Energy Survey: harmonic space detection from Year 3 data - Gomes, Daniel Charles Heringer (2022)
In this work, we aim at measuring the angular diameter distance of a given redshift through analysis of baryon acoustic oscillations (BAO) on the angular power spectrum of galaxies captured by the Dark Energy Survey (DES) during its third year of operation. To achieve this goal, we first make a brief review of the history of cosmology, showing the main characteristics and methods of this discipline. We explain the concept of BAO and its relation with cosmological distances. We offer an overview of the Dark Energy Survey experiment, with emphasis on its tomographic BAO detection effort. We present the computational methods used by the DES collaboration on its analysis of Year 3 data, and we show results we obtained from our independent analysis of these data, following the same methodology as the collaboration. We find the value of DA(z = 0.835) = 10.36(34)rs for the angular diameter distance, which is compatible with the collaborations result and has a relative error of the order of 3%. We compare this value with those found by other large cosmological experiments, in order to show how our work takes a step towards better estimates of cosmological parameters.